Bagaimana Relasi Pesantren dengan Konsep Merdeka Belajar? Mengurai Kajian Historis-Filosofis - Muhammad Hanief; Muhammad Fahmi Hidayatullah (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Freedom to learn is a flagship program of the Ministry of Education and Culture of the Republic of Indonesia. Students are taught to have more value than their potential and creativity. This is in line with the current educational needs to produce generations of skilled and critical thinking to solve problems and have moral nobility as self-adornment. Islamic boarding schools as educational institutions have contributed greatly to the country through the quality of skilled and virtuous human resources. The purpose of this study is to reveal the relationship between Islamic boarding schools and the concept of independent learning from a historical and philosophical point of view. The research methodology is a literature study with hermeneutic analysis of referential writing. The result of the research is that the aim of Islamic boarding school education is essentially to develop Muslims so that they deepen religious understanding and gain the pleasure of Allah. Furthermore, the pesantren curriculum consists of monotheism, fiqh, and tasawuf. Meanwhile, the relationship between pesantren and independent learning is based on integrative principles, character, tasawuf, and independence.